Ci?ncia, ra?a e literatura : tert?lia dial?gica cient?fica nas oficinas do ProEMI - Pereira, Jos? Marcos (2019)
This dissertation deals with an experience of stimulating reading education through the scientific dialogical tert?lia methodology experienced with high school youths from a public school located in the interior of Bahia, having as participants or participants of the Innovative High School Program. Initially, an approach was made to the historical process of invention of writing, as a way to meet the need for timeless communication, such as the recording of everyday experience and the transmission of knowledge, and then it was implemented in the Scientific Dialogic Tert?lia as the methodology. the use of the reader through shared readings with socialization of the comprehension of the text; To this end, the naturalist novel ?OCorti?o? was used for its rich narrative and approach to racial issues in Brazil in the 19th century. In this experience is also presented or author of this work, Alu?sio Azevedo, for his avant-garde approach to political and social issues as fierce criticism of the slave regime and the monarchy. The methodology was based on action research, inserted in the qualitative approach in descriptive analytical perspective, divided into two phases, the first of exploratory character to detect the reading level in which the research studies were found and the second phase was the production and analysis of data collected during workshops used in the assumptions of dialogic dialogue associated with situations experienced by characters of Corti?o, as questions that generate interpretations that refer to the studies of science and biology, also promoting reflections on issues related to scientific racism and social determinism. . This research recommends the application of the Scientific Dialogic Tert?lia, as a methodology for fostering reading education, in the various and varied applications of knowledge promotion, since it promotes exchanges of flavors that stimulate the ability of performances in the analysis of worked texts, since One of the basic premises of this methodology or stimulus to interpretation, thus this activity awakens the capacity and critical sense of the participants, basic prerequisites for the formation of individuals able to respond as social demands. In this sense, as reading activities in this different perspective can promote learning, the bridges established between facts are detected in the scientific texts of universal literature with real life facts, thus being the most significant learning.